(untitled) - Kimbrough, James A. ([New York], 1977)
The manual describes a curriculum in orientation and mobility developed as part of the Adjustment to Blindness Program of the Greater Pittsburgh Guild for the Blind. Objectives and learning experiences are listed for the following 10 units: use of sighted guides, basic indoor orientation and cane skills, residential sidewalk travel, residential/suburban non-sidewalk travel, rural non-sidewalk travel, light controlled intersections, business area travel, business establishment travel, metropolitan travel, and commercial non-sidewalk travel
Keywords: Deafblind people; Orientation and mobility